Multiple-target tracking techniques for radar - Rajendran, Kaviya (2017)
This project looks at the techniques for target tracking in radar systems. The overall approach is to simulate the simplest version of the radar system first before exploring more complicated features. The first phase of the project involves simulation of a basic monostatic radar system in MATLAB, with a single stationary target. This forms the foundation. More advanced scenarios like multiple stationary targets/one moving target are dealt with later on in the project. The problems encountered during the course of this project are discussed and explained. This report also examines the limitations of the radar system and analyzes its deviation from theoretical expectations.